Implementasi E-Bisnis Digital Marketing And Branding Terhadap Alur Informasi Pelayanan Sekolah (Islamic Primary School Ibnu Sina Cikarang Selatan Bekasi) - Mukti, Aryani Kusuma; Chasanah, Rima Huswatun; Prihatin, Dewi Mustikaning; Rusdianthi, Rani; Afiani, Akzir Fitri; Sikki, Nurhaeni (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Advances in digital technology have encouraged various sectors to adopt innovations to increase efficiency, including in the field of education. E-business, which refers to the use of digital technology in various business processes, is now a strategic solution to support more optimal management of information and services. This research aims to evaluate the implementation of e-business through digital marketing and branding in improving the flow of service information at Ibnu Sina Islamic Primary School, South Cikarang, Bekasi. The background to this research is the need for schools to make optimal use of digital technology in internal and external communications, including PPDB activities, interactions with student parents, dissemination of announcements, and regular publication of content. The problem formulation focuses on how effective the online system is in increasing information efficiency and building the school's image. The approach used in this research is a qualitative method, carried out through interviews, observation and analysis of digital documents. The research results show that the use of digital devices, such as school iPhones, as well as the use of social media have succeeded in increasing communication efficiency, expanding the reach of information, and strengthening the school's image in the eyes of the public. The conclusion of this research is that effective integration of e-business technology can support fast, transparent and professional information management. This research recommendation includes the development of school-specific applications to maximize digital-based services.